Severe PID with sub-acute intestinal obstruction during third trimester of pregnancy: a rare presentation - Lucksom, Pesona Grace; Thatal, Annet; Rai, Patrika; Thakkar, Spruha Navinbhai; Niranjan, Kapil Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Pelvic inflammatory disease (PID) during late pregnancy is rare. Authors report a case of severe PID manifesting as subacute intestinal obstruction at early third trimester of pregnancy. A 26 years woman at 28 weeks of gestation was admitted in OBG department of Central Referral Hospital (CRH), Sikkim for evaluation of pain in left hypochondrium with tachycardia and mild rise in temperature. Her WBC was 26,900/cmm while urine and blood cultures were sterile. USG showed single live gestation of 27weeks 3days with a heterogeneous mass suggestive of degenerative fibroid. She had recurrent episodes of subacute intestinal obstructions. Her condition deteriorated, hence, elective caesarean with exploratory laparotomy was done. Single live baby was delivered after which abdominal exploration revealed purulent ascites with multiple pockets of pus. Omental cake along with the bowel was adhered to the fundus of uterus. There was no area of perforation in the gut. Bilateral adnexa were adherent to the pre-sacral region which was densely adhered to underlying great vessels. Post operatively antibiotic to cover the anaerobic bacteria were given to which she responded. Baby died after 4 days of birth due to sepsis. One week after discharge she was readmitted with left sided pleural effusion which responded to antibiotics. PID should be considered a cause of abdominal pain and rise in temperature in pregnancy, as early diagnosis can be managed conservatively with antibiotics thus decreasing maternal and perinatal morbidity and mortality.